2022
DOI: 10.3390/ani12030293
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Seasonal Dynamics of Ticks on Ring-Tailed Coatis Nasua nasua (Carnivora: Procyonidae) in Two Urban Areas from Midwestern Brazil

Abstract: Understanding the diversity and ecology of ectoparasites in wild animals is essential for surveillance of vector-borne diseases. Coatis (Nasua nasua) easily adapt to anthropized areas, favoring close contact with domestic animals and humans, with the possibility of exchange of ectoparasites and pathogens. The present study aimed to identify the diversity of ticks parasitizing coatis from forest urban areas of midwestern Brazil, to evaluate the seasonal dynamics of ticks during the seasons of the year, and to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The present study was conducted in the Cerrado biome, an area characterized by grassland to a nearly closed canopy of medium-height trees overlying grass with a tropical savanna climate [4]. Although these three studies were performed with the same animal species, it is known that tick diversity changes according to the studied biome [3,8,39,44,45]. Animals from the present study were found parasitized by non-identified Amblyomma sp.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The present study was conducted in the Cerrado biome, an area characterized by grassland to a nearly closed canopy of medium-height trees overlying grass with a tropical savanna climate [4]. Although these three studies were performed with the same animal species, it is known that tick diversity changes according to the studied biome [3,8,39,44,45]. Animals from the present study were found parasitized by non-identified Amblyomma sp.…”
Section: Discussionmentioning
confidence: 92%
“…Animals from the present study were found parasitized by non-identified Amblyomma sp. larvae, Amblyomma dubitatum, and Amblyomma sculptum nymphs, and A. sculptum and Amblyomma ovale adults [8]. Since the vector of the detected Ehrlichia sp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations